The influence of crystalline admixtures on the mechanical and durability properties of cracked and uncracked concrete - Lekundayo, Ansifrid (Department of Civil Engineering, 2024)
In South Africa context, water scarcity calls for water retaining structures to perform with respect to strength and seepage. Thermal differential and shrinkage strains often cause cracking which allow seepage under the high hydraulic pressure. Continuous maintenance and repair strategies have become vital to prevent seepage and deterioration over their service lives. Self-healing of concrete promotes reduced water permeability without the need for maintenance and repair. Innovative concrete selfhealing methods include the use of microencapsulation, hollow glass tubes, bacteria, and crystalline admixtures. Crystalline admixtures are directly incorporated into the concrete during mixing to react with water and cement particles to induce self-healing. This study intended to determine the influence of crystalline admixtures on mechanical and durability properties of cracked and uncracked concrete. An experimental methodology involved casting ten concrete mixes. Concrete specimens were obtained by coring, cutting, and introducing crack using the threepoint bending test. Experimental tests conducted were, microscopy tests, strength tests, and durability tests. The XRF test results indicated that cement was a significant component of CAs, thus, the hydrations were expected to be similar to ordinary Portland cement. SEM-EDS tests results revealed that the precipitates extracted from the crack area after healing were found to be composed of polymorphs of calcium carbonate and CSH. The presence of Sr2+ and Mg in the concrete matrix influenced by the calcium carbonate precipitates. The influence of the CAs on mechanical properties of concrete revealed that incorporation of crystalline admixtures generally improves the compressive strengths and splitting strength of concretes with higher water filled porosity than the concretes with lower water filled porosity. In practice, these crystalline admixtures were deduced to have little to no noticeable effect on compressive strength when used in high quality concretes. In durability properties, the influence of CAs on OPI, WSI, and water filled porosity tests were determined on uncracked concrete. OPI test results deduced that, CA-4 concrete recorded the highest decrease in permeability of 51.02% and 43.77% for w/b of 0.4 and 0.6, respectively. This was attributed to the swelling of the concrete matrix, precipitation of calcite crystals, and the likely increased dosage of CA-4 used in the Abstract iii concrete mix. WSI test results indicated that all concrete mixes showed “good” quality with sorptivity values at curing ages 4, 8, and 12 weeks except concretes with w/b of 0.4 at 12 weeks with excellent quality. The sorptivity values were deduced to decrease with an increase in curing age due to the continuing hydration which refined the microstructure of concrete and increase resistance to capillary absorption of liquid. Water filled porosity test results were found to be influenced by the w/b ratio. A decrease in w/b led to lower water filled porosity as hydration products fills the void space between cement particles. While, a higher w/b ratio resulted in higher water filled porosity as the extent to which hydration products fill up the voids is limited. The influence of CAs on WSI, water filled porosity, and water permeability tests were determined on cracked concrete. WSI test results indicated that all the concrete mixes showed “poor” quality concrete with the incorporation of CAs having little effect in improving the sorptivity values. The inconsistency in the sorptivity values was attributed to the crack geometry variation along the depth of the concrete specimens. Water filled porosity test results indicated that the influence of the w/b ratio applies to cracked concrete despite the presence of cracks. Water permeability tests indicated that the permeability (k) of concrete decreases over curing time. This was attributed to the precipitation of calcium carbonate crystals by the crystalline admixtures suggesting that these admixtures do have a positive effect in reducing permeability. More insight on the influence of crystalline admixtures on concrete properties can be achieved by refining the quality of the data collected. Variability in test results obtained due to crack geometry can be minimised by utilising uniform crack width specimens in conjunction with free occurring cracks width for correlation of both test results and inservice performance. Furthermore, an extended curing duration should be employed to continue monitoring the healing process to determine the duration of full self-healing if any. Other microscopic techniques such as Thermogravimetric analysis (TGA) and X-Ray Diffraction Analysis (XRD) can be used to determine the reactivity, thermal/oxidative stabilities, and analysis of the structures of the crystalline admixtures. The use of water permeability test under pressure to minimise the test duration is especially useful which allow the comparison between uncracked and cracked concrete.